Learning SciPy for numerical and scientific computing : quick solutions to complex numerical problems in physics, applied mathematics, and science with SciPy /: quick solutions to complex numerical problems in physics, applied mathematics, and science with SciPy. (2015) - Rojas, Sergio J. G; Christensen, Erik A; Blanco-Silva, Francisco J
No abstract available